SO2 emissions derived from TROPOMI observations over India using a flux-divergence method with variable lifetimes - Y. Chen; Y. Chen; R. J. van der A; J. Ding; H. Eskes; J. E. Williams; N. Theys; A. Tsikerdekis; P. F. Levelt; P. F. Levelt; P. F. Levelt (Atmospheric Chemistry and Physics, 2025)
The rapid development of the economy and the implementation of environmental policies adapted in India have led to fast changes of regional SO2 emissions. We present a monthly SO2 emission inventory for India covering December 2018 to November 2023 based on the Tropospheric Monitoring Instrument (TROPOMI) Level-2 COBRA SO2 dataset, using an improved flux-divergence method and estimated local SO2 lifetime, which includes both its chemical loss and dry deposition. We update the methodology to use the daily CAMS model output estimates of the hydroxyl-radical distribution as well as the measured dry deposition velocity to account for the variability in the tropospheric SO2 lifetime. It is the first effort to derive the local SO2 lifetime for application in the divergence method. The results show the application of the local SO2 lifetime improves the accuracy of SO2 emissions estimation when compared to calculations using a constant lifetime. Our improved flux-divergence method reduced the spreading of the point-source emissions compared to the standard flux-divergence method. Our derived averaged SO2 emissions covering the recent 5 years are about 5.2 Tg yr−1 with a monthly mean uncertainty of 40 %, which is lower than the bottom-up emissions of 11.0 Tg yr−1 from CAMS-GLOB-ANT v5.3. The total emissions from the 92 largest point-source emissions are estimated to be 2.9 Tg yr−1, lower than the estimation of 5.2 Tg yr−1 from the global SO2 catalog MSAQSO2LV4. We claim that the variability in the SO2 lifetime is important to account for in estimating top-down SO2 emissions.